PERBANDINGAN HASIL DAN MINAT BELAJAR KIMIA SISWA KELAS X IPA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF SNOWBALL THROWING DAN TALKING STICK PADA KURIKULUM-2013 DI SMAN 10 KOTABENGKULU - Rika Juwita Saputri; Sumpono Sumpono; Rina Elvia (ALOTROP, 2018)
The purpose of this research to determine the difference in learning outcome and interest of students on chemistry learning between class which applied snowball throwing and class which applied talking stick learning model on nomenclatur of  chemical compounds material in curriculum-2013 of  grade X IPA in  SMA Negeri 10 Bengkulu City. Research conducted is a research with the type of quasi experiment. Analysis of the data used are mean values, normality test, homogeneity test, and t-test. Chemistry learning outcome data obtained pretest and posttest value where average improvement value of cognitive learning result for snowball throwing class and talking stick class are 56,970 and 45,606. While the interest of students learning of  both experiment classes procure percentage are 81,567% and 75,373%. The result of t test with significant level (? = 0,05), then got value for tcount   >ttable is 4,734 > 1,669 for learning result and 3,596 > 1,669  for interest learning. The results showed that there were significant differences in learning outcomes and learning interest between classes that applied snowball throwing learning and classes that applied the talking stick learning model.